Efektivitas dan Problem Penulisan Kutipan dan Daftar Pustaka Pada Mahasiswa - Azyka Sofia; Usiono Usiono (PT. Alahyan Publisher Sukabumi, 2025)
Writing quotations and bibliography is an integral part of scientific work that reflects the credibility of the information source and recognition of other people's work. However, problems in writing quotations and bibliography often occur, especially among students. This research aims to examine the effectiveness of writing quotations and bibliography among students and identify various problems faced by students in this process. The method used in this research is a quantitative survey with a random sampling technique of 100 students from various study programs. The research results show that although the majority of students understand the importance of writing quotations and bibliography correctly, many of them still experience difficulties in following existing guidelines, especially regarding the format and how to refer to various types of sources. The main factors influencing this problem are a lack of understanding of academic writing standards as well as a lack of training regarding the use of reference manager software. This research suggests that universities provide further training regarding writing quotations and bibliography, as well as encouraging the use of tools to improve the quality of students' scientific work.